PERANAN KEKERABATAN SEBAGAI ADAPTASI EKONOMI BAGI MASYARAKAT PERANTAU PADANG LAWAS UTARA - Harahap, Hottob (PERSPEKTIF, 2012)
This research is an adaptaion case of the Paluta Regency migrants people to Medan. Method used in this research is qualitative method, by interview, observation to the business owners where they work and to the officials who hold positions in Medan as the key informant. This research is to give the social integration description in solving the unemployment burden.